Growth and Reproduction of the Pacific Oyster Crassostrea gigas Cultured on Tidal Flat in Hebei Spirit Oil Spill Area on the West Coast of Korea Four Years After the Accident - Hong, Hyun-Ki; Park, Heung-Sik; Choi, Kwang-Sik (Frontiers in Marine Science, 2022)
The Hebei Spirit oil spill (HSOS) accident in December 2007 on the west coast of Korea devastated the intertidal oyster farms along the Taean coast, resulting in the shut-down of the farming for three years. In 2010, two years after the accident, the level of residual oil in the water, sediment, and oyster tissue in the spilled area became similar to the level before the accident, although the fitness of the oysters in the spilled area remained unknown. In an attempt to resume the oyster culture in the spilled area, we monitored the growth and reproduction of the Pacific oyster Crassostrea gigas in an area the most heavily impacted. The oyster spats used in this study were harvested from the oil-damaged area in September 2011 and hardened for 9 months before being transplanted into the grow-out facilities in May 2012. The transplanted oysters demonstrated a fast shell growth for the first 5 months, reaching 53.9 mm in shell length (SL) in October 2011. At the end of the survey in November 2013, the oyster became 65 mm, suggesting an additional year of cultivation to reach the market size. Histology indicated that the annual gametogenesis was synchronous, as the males and females initiated the gametogenesis in January when the water temperature was 5.2 °C. The female oysters spawned from July to September, as the water temperature ranged from 21.2 to 24.8 °C. An indirect enzyme-linked immunosorbent assay (ELISA) applied in the reproductive effort measurement indicated that the fully ripe female oysters produced 20-23 % of their body weight as eggs prior to spawning, which was comparable to the reproductive effort of oysters in oil-spill-free areas. The data suggested that off-bottom rack cultured Pacific oysters at the Euhangri beach successfully recovered from HSOS stresses 4 years after the accident.